(untitled) (Asian Journal of Current Engineering and Maths, 2013)
The notions of pre*- closed, pre*-open sets and pre*-closure, pre*-interior of a subset in topological spaces are introduced in this paper. Their connections with other existing concepts such as pre-closed, semi-closed, Î±-closed etc. are investigated.Â MSC 2010: 54A05.